Pelatihan servis bentor di Desa Patalassang Kabupaten Gowa - Darmawang Darmawang; Zulhaji Zulhaji (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
Bentor (motorbike becak) drivers in Patalassang donot have basic knowledge about how to drive a motorcycle(bentor) or ability to repair it, so bentor is operated not inaccordance with the correct procedure. As a result, thosebentors are often damaged, and have to be brought to therepairman service. This causes the bentor drivers to sufferlosses. Losses because they do not only lose time, but alsohave to pay the repair costs (service fees) which aroundRp30,000 to Rp50,000. In fact, the destructions are caused bythe driving errors and lack of care. This problem really doesnot need to occur, if the bentor drivers have basic knowledgeabout how to drive, maintain and repair a motorcycle engine orbentor. The training carried out was training in how to drive,maintain and repair damages that might occur by means ofdemonstrations and direct practice. The training wasconducted, including how to unload the carburettor and thepossibility of the usual damage, setting the valve, overcomingthe ignition system in the spark plug, and oil change time. Thisactivity was supported by the participants or the trainers whoattended the event, by practicing directly how to unload thecarburettor and how to adjust the valve. The information aboutoil change time was only explained. In conclusion, by doingthis activity, the knowledge and skills of the bentor drivers incarrying out repairs and maintenance as well as driving abentor methods can be increased.